If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 = (3x + -2)(x + 3) Reorder the terms: 24 = (-2 + 3x)(x + 3) Reorder the terms: 24 = (-2 + 3x)(3 + x) Multiply (-2 + 3x) * (3 + x) 24 = (-2(3 + x) + 3x * (3 + x)) 24 = ((3 * -2 + x * -2) + 3x * (3 + x)) 24 = ((-6 + -2x) + 3x * (3 + x)) 24 = (-6 + -2x + (3 * 3x + x * 3x)) 24 = (-6 + -2x + (9x + 3x2)) Combine like terms: -2x + 9x = 7x 24 = (-6 + 7x + 3x2) Solving 24 = -6 + 7x + 3x2 Solving for variable 'x'. Combine like terms: 24 + 6 = 30 30 + -7x + -3x2 = -6 + 7x + 3x2 + 6 + -7x + -3x2 Reorder the terms: 30 + -7x + -3x2 = -6 + 6 + 7x + -7x + 3x2 + -3x2 Combine like terms: -6 + 6 = 0 30 + -7x + -3x2 = 0 + 7x + -7x + 3x2 + -3x2 30 + -7x + -3x2 = 7x + -7x + 3x2 + -3x2 Combine like terms: 7x + -7x = 0 30 + -7x + -3x2 = 0 + 3x2 + -3x2 30 + -7x + -3x2 = 3x2 + -3x2 Combine like terms: 3x2 + -3x2 = 0 30 + -7x + -3x2 = 0 Begin completing the square. Divide all terms by -3 the coefficient of the squared term: Divide each side by '-3'. -10 + 2.333333333x + x2 = 0 Move the constant term to the right: Add '10' to each side of the equation. -10 + 2.333333333x + 10 + x2 = 0 + 10 Reorder the terms: -10 + 10 + 2.333333333x + x2 = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 2.333333333x + x2 = 0 + 10 2.333333333x + x2 = 0 + 10 Combine like terms: 0 + 10 = 10 2.333333333x + x2 = 10 The x term is 2.333333333x. Take half its coefficient (1.166666667). Square it (1.361111112) and add it to both sides. Add '1.361111112' to each side of the equation. 2.333333333x + 1.361111112 + x2 = 10 + 1.361111112 Reorder the terms: 1.361111112 + 2.333333333x + x2 = 10 + 1.361111112 Combine like terms: 10 + 1.361111112 = 11.361111112 1.361111112 + 2.333333333x + x2 = 11.361111112 Factor a perfect square on the left side: (x + 1.166666667)(x + 1.166666667) = 11.361111112 Calculate the square root of the right side: 3.370624736 Break this problem into two subproblems by setting (x + 1.166666667) equal to 3.370624736 and -3.370624736.Subproblem 1
x + 1.166666667 = 3.370624736 Simplifying x + 1.166666667 = 3.370624736 Reorder the terms: 1.166666667 + x = 3.370624736 Solving 1.166666667 + x = 3.370624736 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.166666667' to each side of the equation. 1.166666667 + -1.166666667 + x = 3.370624736 + -1.166666667 Combine like terms: 1.166666667 + -1.166666667 = 0.000000000 0.000000000 + x = 3.370624736 + -1.166666667 x = 3.370624736 + -1.166666667 Combine like terms: 3.370624736 + -1.166666667 = 2.203958069 x = 2.203958069 Simplifying x = 2.203958069Subproblem 2
x + 1.166666667 = -3.370624736 Simplifying x + 1.166666667 = -3.370624736 Reorder the terms: 1.166666667 + x = -3.370624736 Solving 1.166666667 + x = -3.370624736 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.166666667' to each side of the equation. 1.166666667 + -1.166666667 + x = -3.370624736 + -1.166666667 Combine like terms: 1.166666667 + -1.166666667 = 0.000000000 0.000000000 + x = -3.370624736 + -1.166666667 x = -3.370624736 + -1.166666667 Combine like terms: -3.370624736 + -1.166666667 = -4.537291403 x = -4.537291403 Simplifying x = -4.537291403Solution
The solution to the problem is based on the solutions from the subproblems. x = {2.203958069, -4.537291403}
| -20.4r+4(1+5)=4.8 | | 6ln(4x)+3=15 | | 24=(3x-2)+(x+3) | | 2(15)+2=15 | | -6+v/2=11 | | -6.2p+3(-2+2p)=-4.6 | | 8+B=11 | | 7200=120000+90000x | | 2y^3-y^2-5y-2=0 | | x+(x*.16)=46000 | | x+(xy)=46000 | | 8/12=36/x | | 15.5y-13.7y=-26 | | y=-.25*(x-8)-1 | | 12*50= | | 6x+6z=7+5y | | -20+18t=-(6t-4) | | 5x+7z=2+7y | | 5sinx+7cosx=2 | | V(x)=x(5-2x)(10-2x) | | 7sinx+7cosx^2=7 | | 2g+5=1g-4 | | a^2+b^2=40000 | | 2(x+5)(x-2)=x(x+5)+90 | | -6x^2-3x-3=0 | | 3x-8=2+4x-8 | | 7x-3(c+6)=14 | | 26x+4=18 | | 2x=80-2x | | 0.36/8 | | 10n^2-29n-44=0 | | 445-6x=0 |